AIDS and the Family Physician: Survey of Practices in AIDS Counselling and HIV Antibody Testing - Goldstein, Mark L. (1990)
In January and February of 1988, a questionnaire was sent to family physicians affiliated with family practice teaching departments in Toronto to determine whether there was any consensus among family physicians as to which patients they counselled about AIDS and to whom they recommended antibody testing for HIV. Ninety-seven out of 126 questionnaires were answered, for a response rate of 77.0%. More than 90% of the physicians reported discussing AIDS and its prevention with patients in high-risk groups, sexual partners of such patients, and those with multiple sexual contacts. More than 90% recommended HIV antibody testing for patients in high-risk groups who requested it. For discussing AIDS with all sexually active patients, however, there was much less consensus in the reported physician practices.